Correlation between small earthquakes and CO2 anomalies in spring waters: a statistical experiment on the probability of seismic occurrence - Fidani, C.; Gherardi, F.; Facca, G.; Pierotti, L. (Frontiers in Earth Science, 2023)
We correlated carbon dioxide (CO2) time series detected at the Gallicano site in Tuscany, Italy, with low-magnitude earthquakes occurred in the surrounding area between 2017 and 2021. The CO2 irregular component distribution was analyzed by a Pearson type VII fit, and its cumulate probability by the Gauss’s hypergeometric function, to statistically evidence anomalous fluctuations. We calculated the Matthews correlation between gas concentrations and low-magnitude earthquakes by defining a binary occurrence of CO2 anomalies and seismic events. A positive correlation was highlighted by a time lag between the digital series, which resulted in CO2 anomaly detections ahead of the earthquake time of two days. The correlated earthquakes were mainshocks of local magnitude 1.2 to 3.6, with epicenters within 40 km from the Gallicano site. Correlations among rainfalls, CO2 concentrations and earthquakes were also considered, showing that only few rainfall events were followed by a CO2 anomaly, mostly a day late.